Revista digital do LAV/UFSM – conversações entre arquivo, gênero e sexualidade - Losekann, Denise Meller (2020)
This dissertation proposes conversations between archive, gender and sexuality and welcomes the Visual Arts Laboratory Digital Journal (RDLAV or Revista Digital do LAV) of the Federal University of Santa Maria (UFSM) as materiality, considering the discursive productions put into circulation by this journal, as well as what has been produced in the field of Education and Arts and the possible relations between gender and sexuality. It is set as the issue-problem of this dissertation: what can the RDLAV do while archive and its conversations in the play of forces between gender and sexuality? Therefore, the assemblages between education, art, gender and sexuality (BUTLER, 2018; LOURO, 2013, 2014) hang together with the concepts of archive, speech, utterance (FOUCAULT, 1997, 2000, 2004), micropolitics and embryos of the world (ROLNIK, 2018a), forming conversations with these fields of investigation. The Revista Digital do LAV (RDLAV) is considered an archive/world permeated by multiple voices, which makes it possible to think a dissipative archive that can happen more through the lapses, the intervals and the failures/absences than through an agglomerated chain of speeches. Thus, the methodology in this study is based on the notion of archive, which corroborates to problematize such notion, and also allows possible twists in the way of operating it. Therefore, the results present an archive/world composed by blocks of sensations and fragments, moved by provisional dives, that happen through conversations and arrangements between images, writings, concepts and cries of silence.